Searching for Genetic Biomarkers for Hereditary Angioedema Due to C1-Inhibitor Deficiency (C1-INH-HAE) - Parsopoulou, Faidra; Loules, Gedeon; Zamanakou, Maria; Csuka, Dorottya; Szilagyi, Agnes; Kompoti, Maria; Porebski, Grzegorz; Psarros, Fotis; Magerl, Markus; Valerieva, Anna; Staevska, Maria; Obtulowicz, Krystyna; et al. (Frontiers in Allergy, 2022)
Existing evidence indicates that modifier genes could change the phenotypic outcome of the causal SERPING1 variant and thus explain the expression variability of hereditary angioedema due to C1-inhibitor deficiency (C1-INH-HAE). To further examine this hypothesis, we investigated the presence or absence of 18 functional variants of genes encoding proteins involved in the metabolism and function of bradykinin, the main mediator of C1-INH-HAE attacks, in relation to three distinct phenotypic traits of patients with C1-INH-HAE, i.e., the age at disease onset, the need for long-term prophylaxis (LTP), and the severity of the disease. Genetic analyses were performed by a validated next-generation sequencing platform. In total, 233 patients with C1-INH-HAE from 144 unrelated families from five European countries were enrolled in the study. Already described correlations between five common functional variants [F12-rs1801020, KLKB1-rs3733402, CPN1-rs61751507, and two in SERPING1 (rs4926 and rs28362944)] and C1-INH-HAE severity were confirmed. Furthermore, significant correlations were found between either the age at disease onset, the LTP, or the severity score of the disease and a series of other functional variants (F13B-rs6003, PLAU-rs2227564, SERPINA1-rs28929474, SERPINA1-rs17580, KLK1-rs5515, SERPINE1-rs6092, and F2-rs1799963). Interestingly, correlations uncovered in the entire cohort of patients were different from those discovered in the cohort of patients carrying missense causal SERPING1 variants. Our findings indicate that variants other than the SERPING1 causal variants act as independent modifiers of C1-INH-HAE severity and could be tested as possible prognostic biomarkers.